Penyelesaian Masalah Penjadwalan Job-Majemuk dengan Pemakaian Sumberdaya- Majemuk Menggunakan Algoritma Genetika - Aji, Taufiq (UIN Sunan Kalijaga Yogyakarta, 2012)
Scheduling problems with regard to the problem of determining the order to carry out a number of tasks. This issue covers a wide range of areas such as manufacturing, installation project, production planning, hospital management and reservation system. This problem can be seen as an optimization problem of dealing with a number of constraints. An increase in the complexity of the problem requires the existence of an efficient and effective techniques. This study addresses the issue of scheduling multiple job-where there are several different types of resources that are working on an operation or activity simultaneously. Genetic algorithms are developed to solve these problems. Genetic algorithm testing performed against a number of hipotetik example. The output agoritma of genetics compared against optimal technique of the output and the output algorithm based on Lagrange relaxation on the same issue. The results of the comparison with optimal techniques and algorithms based on Lagrange relaxation indicates a significant improvement of computing efficiency, but nevertheless occur a little decrease in effectiveness.